THE QUALITY OF ENGLISH LANGUAGE TESTING IMPLEMENTED IN KBRI SCHOOL, SEKOLAH INDONESIA KUALA LUMPUR, MALAYSIA - Nur Kholilah (Department of English Language Education, UIN Sunan Ampel Surabaya, 2016)
This study is aimed to know how the quality of second grade senior high school Sekolah Indonesia Kuala Lumpur Malaysia English language testing like in term of content validity, index of difficulty, index of discrimination, and the effectiveness of distracters. The design used in this study is a qualitative research. Qualitative in this research is descriptive research. Then, use quantitative descriptive research to calculate and compute the data to prove the qualitative data and conclude the result of this research. The object of this research is second grade of senior high school of Sekolah Indonesia Kuala Lumpur Malaysia and only focus in multiple choice test items. The sample of this research is second grade of Science class and second grade of Social class which conclude all students in the class. The result of this study reported that the English language testing has good content validity. It also reported that the index of difficulty of the English language testing are acceptable. Besides, the index of discrimination of this test is satisfactory. Moreover, it has good distracters.